Development of a novel stall design for dairy cattle: Part I. The effect of an increased slope on lying behavior, rumination, cleanliness, and preference - A.M. Wilson; T.C. Wright; J.P. Cant; V.R. Osborne (Animal, 2022)
The longitudinal slope of a stall is important for positioning cows in the stall and maintaining cleanliness of the stall surface. The objectives of this study were to determine the short-term effect of increasing free-stall slope from 4.5% to 9.3% on dairy cow lying behavior, rumination, milk production, cleanliness, and preference. In experiment 1, 60 multiparous Holstein cows were divided randomly into two groups and exposed to a 4.5% stall slope (standard in the research facility) and a 9.3% stall slope in a replicated crossover design with four 7-day periods. Each group of cows were housed in a pen with 30 free-stalls and switched between treatments weekly. Lying behavior and rumination were recorded continuously, milk yields were recorded twice per day, and cleanliness scores were collected on the last day of each week. Experiment 2 consisted of an 8-day preference test conducted with 14 cows from experiment 1 in an experimental pen with 32 stalls (16 stalls with a 4.5% slope and 16 stalls with a 9.3% slope). Continuous video monitoring was used to record time spent lying, standing, and perching in each treatment during the last 5 days, and lying time was used to assess preference. In experiment 1, cows spent 12 min/day less time lying down (12.8 vs 12.6 ± 0.28 h/d) and had 0.6 more bouts/day (9.5 vs 10.1 ± 0.38 no./d) with a shorter duration by 6 min/day (1.4 vs 1.3 ± 0.03 h/bout) in stalls with a 9.3% slope. Rumination was 5.5 min less per day in stalls with a 9.3% slope (578.4 vs 572.9 ± 16.56 min/d) and milk yield did not differ between treatments (33.6 vs 33.4 ± 0.78 kg/d). Stall slope did not affect cow cleanliness (1.6 vs 1.6 ± 0.05 points on a 1–5 scale). In experiment 2, cows showed no clear preference for lying, standing, or perching in either stall slope (4.5% and 9.3%) when given a choice. These results indicate that increasing stall slope from 4.5% to 9.3% marginally altered lying behavior, but did not interfere with stall use or influence cow preferences.